2020
DOI: 10.1186/s12886-020-01523-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fundus changes following silicone oil and sterilized air tamponade for macular-on retinal detachment patients

Abstract: Background To investigate different tamponade effects of intravitreal silicone oil (SO) and sterilized air on macular vasculature and structure after successful retinal repair for macular-on rhegmatogenous retinal detachment (RRD) patients. Method 21 eyes (21 patients) with macular-on RRD underwent single pars plana vitrectomy following intravitreal SO or sterilized air (Gas) tamponade. Optical Coherence Tomography (OCT) and angiography were used to evaluate retinal layer thickness and flow density (FD) chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 43 publications
5
38
0
Order By: Relevance
“…Based on the inclusion and exclusion criteria, 16 articles were found to be eligible: five studies had arms only evaluating the CMT [ 24 29 ], three studies only evaluating the inner retinal layer thickness [ 7 , 8 , 28 ]. five studies evaluating both CMT and retinal layer segmentation thickness [ 14 , 15 , 17 , 30 , 31 ], and three studies only evaluating the SFCT [ 16 , 32 , 33 ].In the search of Persian databases, no relevant studies were found. Figure 1 presents the flow chart of the selection process used to identify studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the inclusion and exclusion criteria, 16 articles were found to be eligible: five studies had arms only evaluating the CMT [ 24 29 ], three studies only evaluating the inner retinal layer thickness [ 7 , 8 , 28 ]. five studies evaluating both CMT and retinal layer segmentation thickness [ 14 , 15 , 17 , 30 , 31 ], and three studies only evaluating the SFCT [ 16 , 32 , 33 ].In the search of Persian databases, no relevant studies were found. Figure 1 presents the flow chart of the selection process used to identify studies.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies with five effect sizes [ 14 , 15 , 17 , 30 ] examined the effect of SO tamponade on the CMT after SO removal compared to gas tamponade in patients with RRD. The SO tamponade could significantly reduce the CMT (WMD = − 14.91; 95% CI: − 22.23, − 7.60; P < 0.001, I 2 = 71%) compared to gas tamponade in patients with RRD, with substantial heterogeneity between studies (Fig.…”
Section: Meta-analysis and Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] It has also been reported that unexplained visual impairments occurred from damages to retinal structures in eyes treated with SOT. [16][17][18] There are also reports that eyes with non-complex RD treated by SOT had poorer postoperative retinal sensitivity and visual acuity than eyes treated by GT. 19 20 Thus, there is a concern that the toxicity of silicone oil may be greater than that reported.…”
Section: Introductionmentioning
confidence: 99%
“…After a long follow-up period, lower values of VD were measured than the control eyes in the macula. Zhou et al showed that SO had a more negative effect on vasculature and structure of the super cial, deep and choriocapillaris plexus when compared to gas [17].…”
Section: Discussionmentioning
confidence: 99%